Analysis of Electromyographic Amplitude Parameters of Thigh and Calf Muscles During Vertical Jump Execution - Dilshodbek Mamajonov; Merazhidin M. Borkoshev (Indonesian Journal of Sport, Health and Physical Education Science, 2026)
Background: A key indicator of an individual's capability to generate explosive strength, the effectiveness of their neuromuscular coordination, and their stamina is assessed through the vertical jump test. Sports science research commonly uses surface electromyography (sEMG), a non-invasive technique for measuring muscles' electrical activity. In this study, we utilized electrical signal magnitude-based measurements to analyze the electrical activity of the Rectus Femoris, Gluteus Maximus, Gastrocnemius Medialis, and Biceps Femoris Caput Longus muscles in the thigh and calf during vertical jumps. Methods: The study involved seventeen male athletes as participants. The FREEEMG system captured EMG signals at a sampling rate of 1000 Hz, and using MATLAB, the parameters RMS, MAV, MAD, and WAMP were computed. Result: According to the findings, the Rectus Femoris and Gluteus Maximus muscles are crucial for producing explosive power in the propulsion phase, and their amplitude characteristics remained fairly consistent across multiple jumps. Conversely, the Gastrocnemius Medialis and Biceps Femoris muscles showed a steady decline in amplitude, which indicated the start of fatigue. Conclusion: In conclusion, the thigh muscles were primarily responsible for generating force, whereas the calf muscles mainly aided in maintaining postural stability and the last stage of propulsion.